2015
DOI: 10.5551/jat.23770
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Carbon Dioxide Treatment using a Gas Mist Generator Enhances the Collateral Blood Flow in the Ischemic Hindlimb

Abstract: Aim: Highly concentrated carbon dioxide (CO2) is thought to be useful for ischemic diseases. We investigated whether treatment with a few micrometers of CO2 molecules atomized via two fluidnozzles (CO2 mist) exerts an angiogenic effect in a mouse ischemic hindlimb model. Methods: Mice with unilateral hindlimb ischemia were divided into untreated (UT), 100% CO2 gas alone-treated (CG), mixed air (O2; 20%, N2; 80%) mist-treated (AM) and 100% CO2 mist-treated (CM) groups. The lower body of the mice was encased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…eNOS is a key factor for the enhancement of muscle oxidative capacity via up-regulation of PGC-1α expression. In a previous study, application of CO 2 to a hind limb ischemia model enhanced eNOS expression in the skeletal muscle (Irie et al 2005;Izumi et al 2015). Additionally, application of transcutaneous CO 2 to sedentary rats for 12 weeks increased the mRNA level of PGC-1α and SIRT1 and mitochondria number .…”
Section: Cs Activitymentioning
confidence: 71%
See 3 more Smart Citations
“…eNOS is a key factor for the enhancement of muscle oxidative capacity via up-regulation of PGC-1α expression. In a previous study, application of CO 2 to a hind limb ischemia model enhanced eNOS expression in the skeletal muscle (Irie et al 2005;Izumi et al 2015). Additionally, application of transcutaneous CO 2 to sedentary rats for 12 weeks increased the mRNA level of PGC-1α and SIRT1 and mitochondria number .…”
Section: Cs Activitymentioning
confidence: 71%
“…These reports suggest that blood flow appears to be a strong modulator of eNOS levels. On the other hand, Izumi et al (2015) showed that CO 2 therapy promotes blood flow in the subcutaneous tissues, Values are presented as mean ± SEM (two-way ANOVA. * and † significantly different from CON with same intervention and CO 2 (-) vs. CO 2 (+), respectively, at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several medical and surgical interventions are available for the treatment of peripheral artery disease (Carmeliet 2003;Cooke and Losordo 2015;Dhalla et al 2017;Kehler et al 2013;Li et al 1998;Potente et al 2011); however, none of these therapies are satisfactory. Recently, both clinical and experimental studies have indicated the beneficial effects of CO 2 therapy in promoting blood flow in the ischemic limb in peripheral artery disease (Dhalla et al 2017;Hartmann et al 1997a;Hartmann et al 1997b;Irie et al 2005;Izumi et al 2015;Pagourelias et. al.…”
Section: Introductionmentioning
confidence: 99%